Support for the 21st-Century Reserve Force Insights to Facilitate Successful Reintegration for Citizen Warriors and Their Families - Werber, Laura (RAND Corporation, 2013)
This RAND study aimed to facilitate the successful reintegration of guard and reserve personnel after deployment. Data collected from families and resource providers offer insights on how well these personnel and their families fare after deployment, the challenges they face during that time frame, the strategies and resources they use to navigate the reintegration phase, and how to ensure that reintegration proceeds as smoothly as possible.